PROFIL MISKONSEPSI MATERI EVOLUSI SISWA KELAS XII IPA SMA DAN MA DI KABUPATEN KUBU RAYA KALIMANTAN BARAT - Anandita Eka Setiadi; Ari Sunandar; Hanum Mukti Rahayu; Mahwar Qurbaniah (PENA KREATIF : JURNAL PENDIDIKAN, 2022)
Studens at Kabupaten Kubu Raya, Kalimantan Barat, have difficulty in understanding the material of evolution, this is an indication that students are getting misconception, so to solve the problem we need to do an analysis. One of the instruments that can be used to identify misconception is a Three Tier Test. These research aim, to analyze student misconception on evolution material using Three Tier Test at SMA and MA in Kabupaten Kubu Raya. The method that used is descriptive method with qualitative approach. The subjects of the research were students of grade 12 IPA SMAN 1 Sungai Kakap, SMAN 3 Sungai Kakap, MAN 1 Kubu Raya, and MA Al Mustaqim, 2016/2017 in academic year, which consists 144 students. Data collecting techniques that we used was three tier tests. Results show that in SMA the average percentage of students who misconception is 32,09%, in MA the average percentage of students who misconception is 40,46%. The highest percentage of misconception is in evolutionary mechanism concept, 44.86% at SMA students and 52,96% at MA student. Misconception on Darwin's theory of evolutionary concept is 32.35% at SMA students and 26,32% at MA student. On the concept of evidence for evolution is 19.06% at SMA student and 42,11% at MA student